An Intensive Rice Production System Using Hired Mobile Khmer Ethnicity Laborers from Soc Trang, Vietnam (Global Journal of Human-Social Science, 2012)
In Can Tho City area like much of the Mekong Delta of Southern Vietnam both the Kinh and Khmer ethnicity farmers and agricultural wage laborers have had to cope with many changes due to emerging national agricultural policies the move to a market economy increased labor market competition and new land market policies Many landholding farmers lack sufficient labor for intensive rice production and so must rely on seasonal agricultural wage laborers for their harvests Seasonal agricultural wage employment provides important livelihood opportunity for landless and land-poor Khmer ethnicity workers from other parts of the Mekong Delta but this work is precarious The long-term survival of this intensive labor system is uncertain in the context of current moves towards agricultural mechanization
Keywords: Livelihood; market economy; mechanization